Lipidomic analysis of cancer cells cultivated at acidic pH reveals phospholipid fatty acids remodelling associated with transcriptional reprogramming - Lorena Urbanelli; Sandra Buratta; Mariantonia Logozzi; Nico Mitro; Krizia Sagini; Rossella Di Raimo; Donatella Caruso; Stefano Fais; Carla Emiliani (Taylor & Francis Group, 2020)
Cancer cells need to modulate the biosynthesis of membrane lipids and fatty acids to adapt themselves to an accelerated rate of cell division and survive into an extracellular environment characterised by a low pH. To gain insight this crucial survival process, we investigated the lipid composition of Mel 501 melanoma cells cultured at either physiological or acidic pH and observed the remodelling of phospholipids towards longer and more unsaturated acyl chains at low pH. This modification was related to changes in gene expression profile, as we observed an up-regulation of genes involved in acyl chain desaturation, elongation and transfer to phospholipids. PC3 prostate and MCF7 breast cancer cells adapted at acidic pH also demonstrated phospholipid fatty acid remodelling related to gene expression changes. Overall findings clearly indicate that low extracellular pH impresses a specific lipid signature to cells, associated with transcriptional reprogramming.